Correspondence analysis of contingency tables an application on alcohol/marijuana use among college students in the Philippines - Quiles, Laarni N.
Correspondence analysis, a low dimensional graphical representation of the association between the rows and columns of a table was applied to a nationwide survey data on alcohol/marijuana use among college students. The associations of Alcohol/Marijuana Use, Region, Location/Type of School, and Sex were derived from the PROC CORRESP procedure of SAS Statistical Software where the coordinates obtained from the correspondence analyses of the contingency tables of these variables are depicted graphically using the x-y rectangular coordinate system. The association can largely be attributed to the differences in percentages of alcohol/marijuana users and alcohol only users as manifested by the difference of Regions 2 and 6 with high alcohol/marijuana users from Regions 10 to 13 with high alcohol only users. From this study, it is demonstrated how correspondence analysis can graphically show the associations in regions as to distribution of drugs/substance use categories. From these findings, it can be concluded from simple correspondence analysis that the smallest proportion of college students who used alcohol only came from Regions 2 and 6 while the highest proportion of these alcohol only users came from Region 10 and 13. Similarly, the smallest proportion of these students who used both alcohol and marijuana came from Regions 10 and 13 with the highest proportions in Regions 2 and 6. Correspondence analysis was also used to show how drugs/substance use are related to location (urban/rural), type of school (private/public) and sex. With regards to gender, the females are less likely than the males to use both drugs/substance. It also showed that the highest proportions of alcohol only users are in public schools in urban areas. Those college students who are more likely non-users of alcohol and marijuana came from private schools in rural areas.